Information technology of the acquiring professional competencies process in the e-learning management system environment by construction an educational trajectory - Makogon, Helen; Lavrut, Tetiana; Chornyi, Mykola; Matuzko, Borys; Załoga, Wiesława (Національний технічний університет "Харківський політехнічний інститут", 2024)
The subject matter of the article is the construction of an educational trajectory in the environment of an electronic learning management system (ELMS). The goal of the study is the development of information technology ensures the effective use of web-resources in technical disciplines at a university for the acquisition of professional competencies in modern conditions. The tasks to be solved are: to organize the web environment in the e-learning management system(ELMS) for studying the discipline in a technical university on the principles of information technology; to construct an educational trajectory for the acquisition of professional competencies in technical disciplines at a university according to Bloom’s taxonomy; to search ways to optimize the processing of information on web resources using the mathematical apparatus of graph theory; to develop of a recommendation on the construction of an educational trajectory for the professional competences acquisition. General scientific and special methods of scientific knowledge are used.

Предметом вивченняв статті є побудова освітньої траєкторії у середовищі електронно-навчального методичного комплексу. Метою статті є розробка інформаційної технології, яка забезпечує ефективне використання web-ресурсів з навчальних дисциплін технічного профілю у виші для набуття фахових компетентностейв сучасних умовах. Завдання дослідження: Організація середовища електронно-навчального методичного комплексу за принципами побудови інформаційної технології; побудова за таксономією Блума освітньої траєкторії набуття фахових компетентностей з навчальних дисциплін технічного профілю у виші; пошук шляхів оптимізації обробки інформації web-ресурсівз використанням математичного апарату теорії графів; розробка рекомендації щодо побудови освітньої траєкторії набуття фахових компетентностей.
Інформаційна технологія процесу набуття фахових компетентностей у середовищі електронно-навчального методичного комплексу шляхом побудови освітньої траєкторії
Keywords: information technology; educational disciplines; higher education; electronic learning management system; Bloom’s taxonomy; network graph; acquiringof professional competence; інформаційна технологія; навчальні дисципліни; електронний навчально-методичний комплекс; освітня траєкторія; таксономія Блума; мережний граф; сформованість професійної компетентності